The Production of Biogas from Cassava Tubers - Sirirote*, Pramote; Thanaboripat, Dusanee; Klinkroon, Nattapong; Tripak, Sureeporn (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
We utilized a two-phase fermentation process for biogas production under anaerobic conditions using raw cassava tubers as substrate. Fifty grams of dried cassava tubers were ground, mixed with 200 ml of water and added into an acid tank with a working volume of 6 L. The methane tank had a working volume of 21 L. Fermentation was performed at ambient temperature with an average of 33oC using seed culture from Kasetsart University (10% v/v). The highest biogas produced from the methane tank was 13.20 L per day after a fermentation period of 31 days. The efficiencies for the removal of COD, total solids, volatile solids and volatile fatty acids were 86.21, 84.11, 92.44% and 5,745 mg/l, respectively. The methane content of the biogas produced in this study was 64.3%. Keywords: Biogas, methane, cassava, anaerobic condition *Corresponding author: Tel: 662-5625555 E-mail: fscipms@ku.ac.th